Avalia????o da capacidade dos processos de governan??a corporativa de TI baseda no COBIT 5 - Santos, Diana Leite Nunes dos (2013)
COBIT 5 provides a separation of governance and management processes along with a new assessment approach that focus on process capability. This paper describes such assessment performed at a Brazilian government institution that resulted in 40% of the governance processes at level 0 ??? incomplete process and 60% at level 1 ??? performed process. Given the role of governance, fragilities in its processes may reflect negatively in management and additional research should include a closer look at this relationship. For this particular institution, it is expected that all governance processes are performed (level 1) by the next two years, which is a goal towards an efficient and effective governance system. The following barriers to the application of this self-assessment were found: lack of knowledge on COBIT 5 processes from the assessed institution and the extension of the questionnaire which had 33 questions in its final version. When compared to COBIT 4.1 assessment model, the results were lower, as the same organization was classified in level 2 - repeatable but intuitive. The previous model is also easier and faster to apply. This comparison should be done carefully for the models are very different in its design and use. Finally, the proposed objectives were met: the mechanism is repeatable and can be used in the future to create a historic base; it can be performed as a selfassessment and is expected to be completed, in a medium size IT department, in a four hour time limit.